Coexistent Extra Adrenal Pheochromocytoma and Extrapulmonary Tuberculosis: A Case Report and Review of Literature - K, Amita (JCDR Research and Publications (P) Limited, 2012)
Tuberculosis is a major cause of morbidity and mortality in the developing countries, accounting for two billion infected cases and 1.7 million deaths which were attributed to it in 2006, as per the WHO. Cancer was the leading cause of death, next only to coronary artery disease, with 11.3 million new cases and 7.9 million deaths in 2007. The combination of these two deadly diseases poses significant diagnostic and therapeutic challenges to the clinicians and the pathologists. The relationship of tuberculosis and malignancy can be viewed in two ways: tuberculosis can be a risk factor for cancer or tuberculosis and malignancy can coexist in the same biopsy or in the same patient. An early and an accurate diagnosis is a must for planning the appropriate management. We are describing a very rare case of coexistent extra adrenal pheochromocytoma and extrapulmonary tuberculosis in a single patient, which was diagnosed by fine needle aspiration cytology, with a brief review of the literature.